Geographic location of a new venture and the likelihood of a venture capital investment - Ann-Kristin Achleitner; Marko Bender; Christoph Kaserer; Eva Lutz (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2010)
Based on 1182 dyads of German new ventures and venture capitalists involved in a financing round between 2002 and 2007, we examine the impact of spatial proximity on the likelihood of an investment. We find that with each triplication of journey time the relative likelihood of an investment decreases by one third. Venture development stage, the experience of the entrepreneurial team, knowledge-intensity of the industry and the investment volume moderate the relationship between journey time and the likelihood of an investment. Our results suggest that even in economies with a dense infrastructure like Germany regional equity gaps may exist.
Keywords: G24; G31; M13; 330; venture capital; new venture; geographic location; entrepreneurial finance; Entrepreneurship-Ansatz; Risikokapital; Standortwahl; Standorttheorie; Unternehmensfinanzierung